1985
DOI: 10.1007/bf00988575
|View full text |Cite
|
Sign up to set email alerts
|

Selective sequestration of milkweed (Asclepias sp.) cardenolides inOncopeltus fasciatus (Dallas) (Hemiptera: Lygaeidae)

Abstract: The cardenolide content of the gut, wings, and fat body ofOncopeltus fasciatus was examined. The female fat body contained 4-5% of the total cardenolide content of the insect. The cardenolide content of male fat body, and gut and wings of both sexes was below the detection limit of the cardenolide assay. Thin-layer chromatography was used to determine the cardenolide array of various tissues and secretions ofO. fasciatus reared on seeds of a single species of milkweed (A. Speciosa) and adult extracts and dorso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…Nevertheless, like the monarch these conspicuously coloured species also sequester milkweed cardenolides as effective defenses against natural enemies (Duffey & Scudder 1972Isman et al 1977, Duffey et al 1978Scudder & Meredith 1982;Scudder et al 1986;Malcolm 1990Malcolm , 1992. However, because these hemimetabolous insects can also feed on different milkweed species as adults it may not be possible to use host plant-derived cardenolide fingerprints to describe their patterns of movement as in the holometabolous monarch (Moore & Scudder 1985;Malcolm 1990Malcolm , 1992Malcolm et al 1992). Seiber et al (1980) first suggested that monarchs sequester cardenolides more efficiently from plants with low concentrations.…”
Section: It Is Not Yet Clear Whether the Eggs Found Onmentioning
confidence: 95%
“…Nevertheless, like the monarch these conspicuously coloured species also sequester milkweed cardenolides as effective defenses against natural enemies (Duffey & Scudder 1972Isman et al 1977, Duffey et al 1978Scudder & Meredith 1982;Scudder et al 1986;Malcolm 1990Malcolm , 1992. However, because these hemimetabolous insects can also feed on different milkweed species as adults it may not be possible to use host plant-derived cardenolide fingerprints to describe their patterns of movement as in the holometabolous monarch (Moore & Scudder 1985;Malcolm 1990Malcolm , 1992Malcolm et al 1992). Seiber et al (1980) first suggested that monarchs sequester cardenolides more efficiently from plants with low concentrations.…”
Section: It Is Not Yet Clear Whether the Eggs Found Onmentioning
confidence: 95%
“…Oncopeltus fasciatus bugs concentrate CGs mainly from seeds, rather than from leaves ). Most of the CGs are stored in the dorsolateral space, a vacuolated and pigmented epidermal cell layer (Scudder and Meredith 1982a), whereas very low concentrations of CGs are detectable in the haemolymph (Duffey and Scudder 1974;Scudder and Meredith 1982b;Moore and Scudder 1985). The storage of more polar CGs occurs from the first larval instar through to the adult stage, after at least partial conversion of non-polar CGs to more polar metabolites (Duffey et al 1978;Scudder and Meredith 1982b;Moore and Scudder 1985).…”
Section: Cardiac Glycosides In Heteropteramentioning
confidence: 99%
“…Insects feeding on cardenolidecontaining plants are either behaviourally (Helmus and Dussourd 2004) or physiologically adapted (Vaughan and Jungreis 1977;Moore and Scudder 1985;Scudder et al 1986) to deal with cardenolides and often accumulate them in their tissues as an acquired chemical defence against vertebrate predators (for example, Rothschild 1972;Martel and Malcolm 2004).…”
Section: Introductionmentioning
confidence: 99%